The Portrayal of Resistance in Rap Lyrics Between Kendrick Lamar and Rich Brian - Zihan Mailan Nisa; Bunyamin Faisal; Agry Pramita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study discusses the analysis of rap song lyrics using Hippolyte Taine's theory and a comparison of the depiction of resistance and comparison between two rappers with different backgrounds. The purpose of this study is to reveal the cultural differences between Kendrick Lamar and Rich Brian. The method used is qualitative descriptive. The data used are rap song lyrics from each rappers. This study focuses on the analysis of three songs selected from one album from each artist, three songs from Kendrick Lamar's album "To Pump a Butterfly" that is “Alright” (2015), “The Blacker The Berry” (2015), “Mortal Man” (2015) and Rich Brian's album "The Sailor" that is “Yellow” (2019), “Kids” (2019), and “Currious” (2019). In Kendrick Lamar's three albums "To Pump a Butterfly" there are 7 "Race" theories, 8 "Miilieu", and 1 “Moment” each in each song. While in Rich Brian's album "The Sailor" there are 3 "Race" theories, 4 "Millieu", and 1 "Moment" in each song.